Mindfulness Meditation and Interprofessional Cardiopulmonary Resuscitation: A Mixed-Methods Pilot Study. Issue 4 (2nd October 2018) - Kelm, Diana J.; Ridgeway, Jennifer L.; Gas, Becca L.; Mohan, Monali; Cook, David A.; Nelson, Darlene R.; Benzo, Roberto P.
ABSTRACT: Problem: Mindfulness training includes mindfulness meditation, which has been shown to improve both attention and self-awareness. Medical providers in the intensive care unit often deal with difficult situations with strong emotions, life-and-death decisions, and both interpersonal and interprofessional conflicts. The effect of mindfulness meditation training on healthcare providers during acute care tasks such as cardiopulmonary resuscitation remains unknown. Mindfulness meditation has the potential to improve provider well-being and reduce stress in individuals involved in resuscitation teams, which could then translate into better team communication and delivery of care under stress. A better understanding of this process could lead to more effective training approaches, improved team performance, and better patient outcomes. Intervention: All participants were instructed to use a mindfulness meditation device (Muse™ headband) at home for 7 min twice a day or 14 min daily over the 4-week training period. This device uses brainwave sensors to monitor active versus relaxing brain activity and provides real-time feedback. Context: We conducted a single-group pretest–posttest convergent mixed-methods study. We enrolled 24 healthcare providers, comprising 4 interprofessional code teams, including physicians, nurses, respiratory therapists, and pharmacists. Each team participated in a simulation session immediately before and after the mindfulness training period. Each session consisted of two simulated cardiopulmonary arrest scenarios. Both quantitative and qualitative outcomes were assessed. Outcome: The median proportion of participants who used the device as prescribed was 85%. Emotional balance, as measured by the critical positivity ratio, improved significantly from pretraining to posttraining ( p = .02). Qualitative findings showed that mindfulness meditation changed how participants responded to work-related stress, including stress in real-code situations. Participants described the value of time for self-guided practice with feedback from the device, which then helped them develop individual approaches to meditation not reliant on the technology. Time measures during the simulated scenarios improved, specifically, time to epinephrine in Scenario 1 ( p = .03) and time to defibrillation in Scenario 2 ( p = .02), improved. In addition, team performance, such as teamwork ( p = .04), task management ( p = .01), and overall performance ( p = .04), improved significantly after mindfulness meditation training. Physiologic stress (skin conductance) improved but did not reach statistical significance ( p = .11). Lessons Learned: Mindfulness meditation practice may improve individual well-being and team function in high-stress clinical environments. Our results may represent a foundation to design larger confirmatory studies.